The Role of Payment Technology Innovation in Environmental Sustainability: Mediation Effect From Consumers’ Awareness to Practice - An, Jiaji; Di, He; Yao, Meifang; Jin, Shuaiqi (Frontiers in Environmental Science, 2022)
Based on the traditional internal factor model, high environmental awareness should bring higher engagement in environmental practices. In reality, however, many studies have found no significant correlation between the two. To explain this, frontier research is focusing on what external factors influence environmental sustainability. As a typical example of such external factors, this article focuses on the innovation of Internet payment technology. Based on a survey of 623 individuals living across mainland China, we conduct path analysis, stepwise regression analysis, and a mediation test on Internet payment technology, environmental awareness, environmental protection practices, and demographics such as age, income, and sex. We find that Internet payment technology plays a significant mediator role between environmental awareness and environmental behaviors, and that demographics also affect sustainability. Internet payment technology can expand the range of ways in which consumers participate in environmental protection and encourage them to put more green practices through emotional and physical incentives. We thus demonstrate the positive impact of technological innovation on environmental sustainability and unfold the underlying mechanism. Besides providing a reference for other researchers, our study also proposes some applications relevant to the scientific community.